Malaysian accounting: an inquiry into the struggle, the crisis, and the future - Mustafa, Hasri (2017)
Are we satisfied providing of what accounting has provided? How many books about accounting and accountability have we read and forgotten the instant we finished reading them? What difference they have made then? Will readers understand the deepest emotion of the texts? So many years have passed and many witness what happen to Malaysian history to accounting field was left unnoticed. Attempt to answer the questions will subsequently implicate the conditions of theorizing accounting based upon an inquiry into Malaysians own struggle, crisis and future prospect.The aim of the study is to encourage accounting researchers, especially Malaysians, to view accounting with responsibility,answer ability, blameworthiness, liability, and other terms associated with the expectation of account-giving.